NEURODIDACTICS AS A TECHNOLOGY FOR THE DEVELOPMENT OF MENTAL ACTIVITY OF PRIMARY SCHOOL STUDENTS - Жұмабаева, Жәзира; Базарбекова, Рабиға; Калбергенова, Шолпан (Pedagogy and Psychology, 2023)
The article is devoted to the development of mental activity of primary school students through the development of neurodidactic content in the primary education system. Based on the study of scientific literature, an analysis of the current state of neuropedagogy, neurodidactics was made, and the experience of using neurodidactic content in the world and domestic educational programs and educational process was considered. Using neurodidactic content such as neuro-exercises, neuro-tasks in the educational process of the primary school, the relevance of the problem of developing the mental activity of primary school students was determined. The results of the survey conducted with primary school teachers working in different regions of the republic showed that teachers' attitudes and attitudes towards neurodidactics are positive. According to them, neurodidactic content and brain-based teaching strategies and methods create an opportunity to increase the development and activity of students' mental activity.